Effect of The Combination Phytobiotic and Probiotic on The External Quality of Mojosari Egg-Laying Ducks - Nuningtyas Yuli Frita; Natsir Muhammad Halim; Tistiana Heli (BIO Web of Conferences, 2024)
This study aims to evaluate the use of a combination between phytobiotics and probiotics on the external egg quality of laying ducks. One hundred Mojosari laying ducks were divided into 4 treatments and 5 replications, each replication with 5 ducks. The treatments were T1: control, T1: 0.25% combination, T2: 0.5% combination and T3: 0.75% combination. The variables observed were egg weight, egg length, egg width, and egg shape index. Observations on variables were carried out once a week for four weeks, each replicate using 2 eggs. The data was statistically analyzed using analysis of variance (ANOVA) from a Completely Randomized Design (CRD), and then the significant difference continued with Duncan’s Multiple Range Test. Based on the results, it shows that the different levels of the combination of phytobiotics and probiotics showed significantly different results (p<0.05) on egg weight, however did not significantly different (p>0.05) on the egg length, egg width, and egg shape index. It can be concluded that the use of a 0.5 to 0.75 combination of phytobiotics and probiotics can improve the external quality of duck eggs.